The Prospects for the Social Economy in a Changing World - Juan Antonio Tomás Carpi (CIRIEC-España, Revista de Economía Pública, Social y Cooperativa, 2008)
Even if the 'social economy' has traditionally been marginalized and a subordinated form of production within capitalist societies, the economic, social, territorial and environmental problems of the present times have tended to make it a strategic instrument. This is not only because of its qualities as an economic and management instrument, but also because it is an expression of a dynamic and creative civil society. The aim of this paper is to show the potential of the social economy, the way it has been encapsulated during the postwar period and the conditions that now favour its full development. In the face of new challenges, the efficiency criterion, hitherto used to assess alternative forms of production, is shown to be insufficient. Some complementary criteria are proposed that in better with the new path society must follow if fundamental values have to be satisfied. Starting from these criteria and relating them to management in fields of growing social importance, a new insight into the advantages of the social economy over the market and public sectors can be obtained. Stimulated by such challenges, and connected to the new social movements, a new social economy is emerging with significant potential and a strategic role in managing society. But this development is not without serious problems, and objective and subjective conditions need first to be fulfilled.